Design and fabrication of automatic scrap collecting vehicle. Issue 1 (December 2020) - Ashokkumar, S; Thiyagarajan, C; Anvar, Misbah; Karthikayan, Kiran; Midhun, M
Abstract: The main objective of this paper is eliminating the need to manually collecting the scrap in small scale industries. For the purpose, we are designing automatic scrap collecting vehicles running automatically. In the available methods of scrap collecting manpower, fuel power vehicle is used. By the end of 2020, fuel deposits in the world completely depleted. To avoid this type of problem and reduce manpower requirement we need another type of automation is called battery operated automatic scrap collecting vehicle. The rechargeable battery is supplying power to the automatic scrap collecting. The vehicle is having the A. C Blower which is used to collect the scrap automatically.